INTERAKSI INFORMASI ASIMETRI, BUDAYA ORGANISASI, DAN GROUP COHESIVENESS DALAM HUBUNGAN ANTARAPARTISIPASI PENGANGGARAN DAN BUDGETARY SLACK (Studi kasus pada rumah sakit umum daerah se jawa tengah) - Hj. Falikhatun. (Media Riset Akuntansi, Auditing & Informasi, 2008)
This objective of the research was examined the effect of budgetary participation on budgetary slack using information asymmetry, organizational culture, and group cohesiveness as moderating variables. Hypotheses that proposed is a high budgetary panicipation will have positive effect on budgetary slack. The information asymmetry, organizational culture, and group cohesiveness will have positive effect on budgetary slack The population is Region General Hospital that located in Central Java. Purposive random sampling used to take the samples. Data collection method that used is mail questionnaires method. Data analyze mediod is validity and reliabilit y analysis, clasic assumption analysis and hypotheses analysis that used multiple regression. The results are all variables valid and reliable and&CI clasic assumption. The result of hypotheses analysis show that budgetary participation have positive and significance effect on budgetary slack. Furthermore, information asymmetry and group cohesiveness have moderating variables in the relationship budgetary participation and budgetary slack,. but organizational culture with employee oriented do not have moderating variables in the relationship budgetary participation and budgetary slack.Key words: budgetary participation, information asymmetry, organizational culture, group cohesiveness, budgetary slack